Original paperSerological test results of sexually transmitted diseases in patients with condyloma acuminata - Ünal, Emine; Gönül, Müzeyyen; Çakmak, Seray; Iyidal, Ayşegül Yalçınkaya; Kılıç, Arzu; Gül, Ülker; Doner, Pinar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Human papillomavirus (HPV) is one of the most common causes of sexually transmitted diseases (STD). The incidence of condyloma acuminata (CA) has increased in recent years. Aim: To determine demographical features and serological test results of STD in patients with CA. Material and methods: A cross-sectional survey was conducted on 94 patients presenting to a dermatology clinic in Ankara, Middle Anatolia, Turkey. Dermatological examinations were made and the patients completed a questionnaire which consisted of questions about their marital status, partners and condom use. In all cases, VDRL/RPR, anti-HIV, HBsAg, anti-HCV and in 57 cases – HSV type 1–2 IgM and IgG were studied. If the value of VDRL or RPR was positive, TPHA was conducted. Results : In our study, 83 men and 11 women had CA. We could not analyze whether our cases had multiple partners and a habit of condom use as some of the patients did not answer questions about their sexual life. We observed VDRL and TPHA positivity in 3 (3.1%) cases, none of those cases had clinical findings of syphilis and they denied using any therapy for syphilis. HBsAg positivity was found in 3 cases. No anti-HIV and anti-HCV antibody positivity was detected. Conclusions : The seroprevalence of HBsAg in our study was similar to that of the general population of Turkey. But as we found positive syphilis serology in 3 patients, we suggest that syphilis serology should be investigated in patients with CA.